2012
DOI: 10.1108/02652321211262203
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility to build strong Brazilian bank brand

Abstract: Purpose -The purpose of this study is to identify and analyze the set of corporate social responsibility actions of a Brazilian bank as support to the strengthening of an organizational brand. The specific scope is to discuss the reflections of sustainable actions adopted for the recognition of the organization's brand. Design/methodology/approach -A case study, based on Yin, and in-depth interviews with those responsible for the sustainability department of the studied organization were adopted. Findings -Lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 37 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…construct and present desired organizational images" (S. G. Scott & Lane, 2000, p. 56). Scholars who have tested S. G. Scott and Lane's (2000) model have critiqued the theoretical framework, noting that although one of the main goals of leaders is to manage organizations' identities, other actors, including advertising agencies and suppliers, also communicate and influence identities (Scharf, Fernandes, & Kormann, 2012). In their study of identity construction of major sporting events, such as the Olympic Games, Parent and Foreman (2007) found that "certain stakeholders, such as the media, play a particularly important and distinct role in the process, a role not found in the Scott and Lane OIC [organizational identity construction] framework" (p. 32).…”
Section: Stakeholder Identification (Stakeholder To Organization)mentioning
confidence: 99%
“…construct and present desired organizational images" (S. G. Scott & Lane, 2000, p. 56). Scholars who have tested S. G. Scott and Lane's (2000) model have critiqued the theoretical framework, noting that although one of the main goals of leaders is to manage organizations' identities, other actors, including advertising agencies and suppliers, also communicate and influence identities (Scharf, Fernandes, & Kormann, 2012). In their study of identity construction of major sporting events, such as the Olympic Games, Parent and Foreman (2007) found that "certain stakeholders, such as the media, play a particularly important and distinct role in the process, a role not found in the Scott and Lane OIC [organizational identity construction] framework" (p. 32).…”
Section: Stakeholder Identification (Stakeholder To Organization)mentioning
confidence: 99%
“…According to UNIDO (United Nations Indus trial Development Organization, 2002), satisfying the economic responsibility creates jobs and income in developing countries. The study of Roberto Scharf et al (2012) revealed that CSR actions reflect different demands in supporting the financial institution brand, including social, economic and environmental demands. The second one of Carroll's (1991) CSR model is legal responsibilities which include performing business works by fulfiling the anticipations of government and law.…”
Section: Csr Components and Brand-equity Relationshipmentioning
confidence: 99%
“…As a part of the service industry, banking organizations’ brand value can be enhanced by undertaking CSR events like promoting social programs and welfare activities. After the global financial crisis, CSR can be used as an important tool to rebuild the trust and corporate image for the banking sector (Kaeokla & Jaikengkit, 2013; Roberto Scharf et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, trust is a tactical aspect that enables any bank and the wider financial system to retain operational consistency and integrity (Aljarah et al, 2020;Kartika et al, 2020;Laguir et al, 2021;Shahid et al, 2022;Shaw, 2014). Adopting and communicating CSR is one way to increase trust in the banking industry (Roberto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…, 2022; Shaw, 2014). Adopting and communicating CSR is one way to increase trust in the banking industry (Roberto et al. , 2012).…”
Section: Introductionmentioning
confidence: 99%